Atrioventricular block in coronary artery bypass surgery: perioperative predictors and impact on mortality - Ricardo Medeiros Piantá (Brazilian Journal of Cardiovascular Surgery, 2015)
AbstractIntroduction:Disturbances of the cardiac conduction system are frequent in the postoperative period of coronary artery bypass surgery. They are mostly reversible and associated with some injury of the conduction tissue, caused by the ischemic heart disease itself or by perioperative factors.Objective:Primary: investigate the association between perioperative factors and the emergence of atrioventricular block in the postoperative period of coronary artery bypass surgery. Secondary: determine the need for temporary pacing and of a permanent pacemaker in the postoperative period of coronary artery bypass surgery and the impact on hospital stay and hospital mortality.Methods:Analysis of a retrospective cohort of patients submitted to coronary artery bypass surgery from the database of the Postoperative Heart Surgery Unit of the Sao Lucas Hospital of the Pontifical Catholic University of Rio Grande do Sul, using the logistic regression method.Results:In the period from January 1996 to December 2012, 3532 coronary artery bypass surgery were carried out. Two hundred and eighty-eight (8.15% of the total sample) patients had atrioventricular block during the postoperative period of coronary artery bypass surgery, requiring temporary pacing. Eight of those who had atrioventricular block progressed to implantation of a permanent pacemaker (0.23% of the total sample). Multivariate analysis revealed a significant association of atrioventricular block with age above 60 years (OR=2.34; CI 95% 1.75-3.12; P<0.0001), female gender (OR=1.37; CI 95% 1.06-1.77; P=0.015), chronic kidney disease (OR=2.05; CI 95% 1.49-2.81; P<0.0001), atrial fibrillation (OR=2.06; CI 95% 1.16-3.66; P=0.014), functional class III and IV of the New York Heart Association (OR=1.43; CI 95% 1.03-1.98; P=0.031), perioperative acute myocardial infarction (OR=1.70; CI 95% 1.26-2.29; P<0.0001) and with the use of the intra-aortic balloon in the postoperative period of coronary artery bypass surgery (OR=1.92; CI 95% 1.21-3.05; P=0.006). The presence of atrioventricular block resulted in a significant increase in mortality (17.9% vs. 7.3% in those who did not develop atrioventricular block) (OR=2.09; CI 95% 1.46-2.99; P<0.0001) and a longer hospital stay (12.75 days x 10.53 days for those who didn't develop atrioventricular block) (OR=1.01; CI 95% 1.00-1.02; P=0.01).Conclusions:In most cases, atrioventricular block in the postoperative period of coronary artery bypass surgery is transient and associated with several perioperative factors: age above 60 years, female sex, chronic kidney disease, atrial fibrillation, New York Heart Association functional class III or IV, perioperative acute myocardial infarction and use of an intra-aortic balloon. Its occurrence prolongs hospitalization and, above all, doubles the risk of mortality.